Efeito da adição de butirato de sódio microencapsulado sobre o desempenho produtivo e a regeneração da mucosa intestinal de frangos de corte submetidos a um modelo de desafio experimental - Imperatori, Fabrício (2018)
The industrial poultry has as important characteristic to be in constant evolution process always seeking better zootechnical results and optimization of productive costs allied to the satisfaction of the final consumer. In recent years, one of the yearnings of the poultry chain linked to the consumer's search for safe and non-antibiotic food has been causing that new production techniques are developed. In this context, organic acids, besides presenting characteristics that put them as an alternative to the use of performance-enhancing antibiotics, are also food additives potentially capable of benefiting the development of production animals, either under normal breeding conditions or in situations of enteric challenge. This research aimed to evaluate the zootechnical, immunological aspects and the intestinal morphology of broilers supplemented with microencapsulated sodium butyrate. For the accomplishment of this study 1080 male chicks of the Cobb Slow line with 22 days of age were used. The birds were distributed in a completely randomized design in a 2 x 2 factorial scheme (supplemented diet or not with sodium butyrate vs. with or without enteric challenge), resulting in 4 treatments and 9 replicates of 30 birds per box. At 22 days of age, the birds in the challenged groups received inoculation in the crop of coccidiosis vaccine containing 20 times the dose recommended by the manufacturer. Two days after (24th day), the challenged group birds received an inoculum containing Escherichia coli (ATCC® 8739™) with a calculated concentration of 109 CFU/bird applied directly in the crop. The evaluation of the average weight, feed intake, weight gain and feed conversion was performed weekly. Samples of intestinal mucosa were collected at 28 and 42 days of age after necropsy of two birds / replicate (18 birds per treatment) for evaluation of intestinal morphometry, inflammatory mucosal condition, analysis of the proliferative capacity of intestinal cells and permeability of the intestinal mucosal. At these same ages samples of excreta were collected directly from the cecum of 7 birds/treatment for the count of Clostridium Sulfite Reducers and microorganisms of the family Enterobacteriaceae. For the calculus of the carcass yield, cuts and deposition of abdominal fat, at 42 days, 45 birds/treatment were slaughtered. The statistical analysis of the data was performed using the GLM procedure and the non-parametric data were analyzed through the Kruskal-Wallis test of the SAS software. Non-inoculated birds showed lower (P<0.05) oocyst count than birds that were inoculated, regardless of the kind of diet, basal or supplemented with sodium butyrate. Birds challenged, regardless of diet, presented worse (P<0.05) productive performance. The microorganisms’ count of the Enterobacteriaceae and Clostridium sulfite reductants present in the cecum of broiler chickens showed that there was no significant effect (P>0.05) of diet or enteric challenge on the microbiota of the cecum of the broiler chickens. Serum FITC-d levels were not altered (P>0.05) by the challenge or the diet, demonstrating no difference in intestinal permeability. The birds that were challenged had a higher rate of cell renewal by increasing the depth and width of the crypt, reducing the villi length ratio:depth of the duodenum crypt and smaller area of absorption in the mucosa of the jejunum in relation to the control birds. In the ileus, the interaction unfolded showed longer bird lengths that were challenged and supplemented with sodium butyrate compared to the challenged ones, but only received a basal diet. Analysis of the proliferative capacity of the intestinal cells and the intestinal morphometry are still being performed. The birds that were not challenged presented higher (P<0.05) carcass, breast and leg weight loss, regardless of diet. Dietary supplementation of broiler chickens from 22 to 42 days of age with sodium butyrate submitted or not to enteric challenge did not influence the productive performance, carcass yield and intestinal health of the birds.